Investigation of time-based pressure control for microfluidics chip design - TOPTAŞ, ERSİN; ERSOY, SEZGİN; ATAKÖK, GÜRCAN (My University, 2023)
The emergence of the microfluidic chip was a game-changer in microbiological analysis platforms. This technology, by combining physics, chemistry, biology, and computing, helps researchers to obtain precise results in a shorter time. However, it requires more advancements in order to lessen its limitations. This study presents the design, modelling, and microbiological analysis of a microelectromechanical system (MEMS) based microfluidic chip. Three different microfluidic chips have been developed during the design process. These chips have different inlet channels and one outlet channel. The modelling process was carried out with Multiphysics Software. Pressure and velocity data in micron-sized channels were checked for each system. The flow directions of the fluids in the inlet and outlet channels were observed according to the pressure change. As a result of the analysis, the highest velocity was found in the microfluidic chip with three inlet channels. In comparison, the highest pressure was measured in the microfluidic chip with four inlet channels. These values are 2.36 x10-17 m/s and 13.5 Pa, respectively. The pressure values of the 4 and 5-channel microfluidic chips were very close. The results showed that as the number of inlet channels increased, the pressure value in the microfluidic chip increased, but the velocity value decreased.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)